Exploring Business Sustainability Factors In MICE Tourism From an MSME Perspective - Yuniati, Nining (Publisher Cv. Inara, 2025)
Event industry as popular known as MICE Tourism business is rapidly growing in Indonesia, various international events have been successfully held in Indonesia, but little is known about how these events are operated and who the parties involved are. Behind the success of the event, many MSME are involved with several constraints that also need government attention, so that they can support the sustainability of event entrepreneurs in the future. The main problem is the lack of achievement standards that can serve as a reference other than simply meeting the terms of reference and spending according to the budget plan outlined in the contract. Based on direct observation and interviews with event business owners, namely a number of involved event organisers and vendors, and with the help of NVIVO software, at least eight important factors were identified: Commitment & Contract, Innovation & Novelty of Event, Mutual Partnership, Payment, Portfolio & Experience, Product Quality, Profit, and Zero Complaint. Each factor and its implications are discussed in detail in this study